Dose dependent effects of protracted ingestion of small amounts of gliadin in coeliac disease children: a clinical and jejunal morphometric study. Issue 11 (November 1993) - Catassi, C; Rossini, M; Rätsch, I M; Bearzi, I; Santinelli, A; Castagnani, R; Pisani, E; Coppa, G V; Giorgi, P L
Abstract : This study aimed to investigate the effects of chronic ingestion of small amounts of gliadin on children with coeliac disease. A four week challenge was performed on 20 children who had been on a gluten free diet for mean (SD) 14 (3) months. They were given a daily dose of either 100 mg (group A, n = 10, mean age 4 (2) years) or 500 mg of gliadin (group B, mean age 5 (3) years). The effects of the gliadin were monitored by morphometric study of the jejunal mucosa, intestinal permeability test with cellobiose/mannitol, and serum antigliadin antibody test. After the challenge, group A patients showed a significant increase in the mean intraepithelial lymphocyte count (before challenge 11 (3), afterwards 19 (6)) and a decrease in the villous height/crypt depth ratio (beforehand 1.5 (0.1), afterwards 1.3 (0.2)), while the intestinal permeability test remained normal and the IgA-antigliadin antibody increased in four of 10 children. After the challenge group B showed more pronounced histological changes, an increase in the mean urinary cellobiose/mannitol % (beforehand 0.028 (0.020), afterwards 0.058 (0.028)), and IgA-antigliadin antibody positivity in six of eight subjects. The discriminant analysis function showed that the pretreatment group, group A after challenge, and group B after challenge were correctly classified in 90% of cases by functions based on the individual intraepithelial lymphocyte count and the villous height/crypt depth ratio. This study shows that chronic ingestion of small amounts of gluten causes dose-dependent damage to the small intestinal mucosa in children with coeliac disease. The predictive value of laboratory tests, such as the antigliadin antibody test and the intestinal permeability test seems to be lower in treated patients than in those with active coeliac disease.